Post‐colonial careering and urban policy mobility: between Britain and Nigeria, 1945–1990. Issue 1 (7th September 2016) - Craggs, Ruth; Neate, Hannah
Abstract : This paper sets out the value of the concept of 'careering' to understanding the global mobility of urban policy across historical and contemporary contexts. Through a case study of one colonial and post‐colonial career in urban development, we demonstrate the material and ideological connections between late colonial development in Nigeria, British reconstruction and international consultancy. Empirically, the paper provides novel post‐colonial perspectives on Britain's post‐Second World War reconstruction spanning the mid‐ to late 20th century, globalising the geographies of the British new town. Conceptually, the paper argues that careering provides a valuable tool for progressing the study of urban expertise and its mobility in four ways. First, it provides a tool for connecting geographically distant urban development projects. Second, careering allows us to explore intersections between urban development policies and geopolitical transformations. Third, careering allows us to see the impact of ideas, skills, experiences, affiliations and contacts formed at different stages of a career on later professional practice, slowing down and lengthening out our understandings of the processes though which urban policy is made mobile. Fourth, careering as a method demonstrates the continued value of biographical approaches to urban policy mobility, highlighting in particular professional lives worked with colleagues and contacts rather than in isolation, and foregrounding the everyday embodied nature of urban expertise. The article concludes by suggesting such approaches could be productive for the writing of new post‐colonial histories of geography and its allied disciplines.